2013
DOI: 10.4236/jct.2013.410178
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pretreatment Levels of Serum Vascular Endothelial Growth Factor (VEGF) and Survival Outcomes in Locally Advanced Cervical Cancer Patients

Abstract: Objective: To evaluate the association between pretreatment levels of serum vascular endothelial growth factor (VEGF) and long-term treatment outcomes in patients with locally advanced cervical cancer (LACC). Methods: Thirty-nine patients diagnosed with LACC (stage IIB-IVA) and obtaining blood for serum VEGF were identified. All patients received complete treatment as radical radiotherapy with or without concurrent chemotherapy. Surveillance for all patients was every 3 months during the first 2 years, and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…However Katanyoo et al (2011) in a study in advanced cervical cancer cases did not observe any correlation between pretreatment circulatory levels of serum VEGF levels, median level, 611.3 pg/ml (range: 0.00-4,067pg/ ml), and progression or with response to radiotherapy.…”
Section: Vegfmentioning
confidence: 79%
“…However Katanyoo et al (2011) in a study in advanced cervical cancer cases did not observe any correlation between pretreatment circulatory levels of serum VEGF levels, median level, 611.3 pg/ml (range: 0.00-4,067pg/ ml), and progression or with response to radiotherapy.…”
Section: Vegfmentioning
confidence: 79%
“…However, the study of Katanyoo et al showed that median serum VEGF level before treatment was 611.3 pg/ mL, which was irrelevant to tumor stage, histological type, tumor size etc. (Katanyoo et al, 2011). The differences of serum VEGF levels in CR and RD patients after treatment were not statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…Comparable results for VEGF were obtained by Srivastava et al [43], Zusterzeel et al [42] and Du et al [44] where positive correlation between the serum VEGF level, tumor stage and its size was found. On the other hand, Katanyoo et al demonstrated that the pretreatment serum levels of VEGF in cervical cancer patients do not correlate with stage and tumor characteristic [45]. This discrepancy between the results is probably the effect of different composition and size of the studied groups.…”
Section: Discussionmentioning
confidence: 99%